Study of the functional role of Bcl-2 family proteins in regulating Ca2+ signals in apoptotic cells. (25th October 2007) - Lao, Y.; Chang, D.C.
Abstract : Recently, it was found that Bcl-2 family proteins can affect the apoptotic process by modifying Ca 2+ released from the ER (endoplasmic reticulum). In this review, we summarize the evidence that Bcl-2 and Bax can modulate Ca 2+ mobilization from the ER to the cytosol and mitochondria. We also found evidence that both Bcl-2 and Bax can interact with IP3 Rs (Ins P 3 receptors) to modify the Ca 2+ efflux from the ER. On the basis of our findings, we suggest that Bax may interact with IP3 Rs to facilitate the release of Ca 2+ from the ER during apoptosis.